Comparison of ImmunoCAP and Immulite serum specific IgE assays for the assessment of egg allergy. Issue 1 (December 2016) - Graham, François; Bégin, Philippe; Paradis, Louis; Lacombe-Barrios, Jonathan; Paradis, Jean; Des Roches, Anne
Abstract Egg specific IgE levels are frequently used in combination with skin-prick tests to guide clinical decisions and to monitor egg allergy evolution in children. We compared both Immulite and ImmunoCAP egg specific IgE assays in egg allergic children, and found a linear correlation between both assays with a mean Immulite:ImmunoCAP ratio of 3. This is relevant information for clinicans wishing to estimate values from one assay to the other, as most literature has been published using the ImmunoCAP system.